2020
DOI: 10.1080/26408066.2020.1788477
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Review of Some Reliability and Validity Issues regarding the Strengths and Difficulties Questionnaire Focusing on Its Use in Out-of-Home Care

Abstract: Purpose: A systematic review was conducted to analyze the inter-rater reliability, cross-informant consistency, test-retest reliability, and temporal stability of the Strengths and Difficulties Questionnaire (SDQ), and its ability to discriminate. Method: We searched three databases for articles about the SDQ (parent, teacher, and self-report version), used samples of children up to age 18 and reported inter-rater reliability, cross-informant reliability, test-retest reliability, temporal stability, specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 98 publications
0
24
0
4
Order By: Relevance
“…That said, EPII scores continued to predict psychopathology at the COVID assessment even when controlling for pre-pandemic psychopathology. Although between-person processes cannot be fully distinguished from within-person change with only two time points ( 33 ), such findings nevertheless suggest a more direct link between disruption and psychopathology.…”
Section: Discussionmentioning
confidence: 87%
“…That said, EPII scores continued to predict psychopathology at the COVID assessment even when controlling for pre-pandemic psychopathology. Although between-person processes cannot be fully distinguished from within-person change with only two time points ( 33 ), such findings nevertheless suggest a more direct link between disruption and psychopathology.…”
Section: Discussionmentioning
confidence: 87%
“…Data on SRH knowledge was collected using an instrument based on the "Illustrative Questionnaire for Interview-Surveys with Young People", a core set of instruments endorsed by the World Health Organization [16]. This instrument is widely used in low-and middle-income countries and has been used in several studies where validity has recently been reported to be high (Cronbach's alpha coefficient of 0.89) [17]. The study tool was pre-tested in Kampala before field data collection.…”
Section: Data Tool Developmentmentioning
confidence: 99%
“…44,[53][54][55][56] To understand the agencies and pathways to resilience among adolescents from at-risk backgrounds, developing tools to measure risk and protective factors is particularly important. Many scales have been developed for measuring risk factors 18,57 and protective factors like resilience, 58,59 attachment, 60 strength and difficulties, 61 and well-being. 62,63 The scales focus on self-reports by adolescents 59 and other external factors contributing to protective factors.…”
Section: Protective Factors and Adaptationmentioning
confidence: 99%
“…66 Instruments like strength and difficulties questionnaire do not measure factors in a holistic approach or socioecological framework to understand positive adaptation in adolescents. 61 Therefore, a tool that assesses the psychosocial risk and psychosocial protective factors in adolescents can provide a better understanding of the lives of adolescents. The need for the present study stems from the lack of a tool that provides a global assessment of psychosocial risk and protective factors covering different levels of the social-ecological model.…”
Section: Risk Factors and Adaptationmentioning
confidence: 99%